The Drosophila MBD2/3 protein mediates interactions between the MI-2 chromatin complex and CpT/A-methylated DNA. - Marhold, J.; Kramer, K.; Kremmer, E.; Lyko, F. (Development, 2004)
Methyl-DNA binding proteins play an important role in epigenetic gene regulation. The Drosophila genome encodes a single protein (MBD2/3) with extended homologies to the vertebrate methyl-DNA binding proteins MBD2 and MBD3. However, very little is known about its functional properties. We have now characterized an MBD2/3 null mutant allele that is viable and fertile. This mutation caused a strong dominant suppression of position-effect variegation and also resulted in a high rate of chromosome segregation defects during early embryogenesis. Confocal analysis of mutant embryos showed local displacement of MI-2 from DNA and indicated that MBD2/3 is associated with only a subset of MI-2 complexes. In addition, band shift experiments demonstrated a specific binding of MBD2/3 to CpT/A-methylated DNA, which reflects the endogenous DNA methylation pattern of Drosophila. Consistently, the localization of MBD2/3 was disrupted in embryos with reduced levels of DNA methylation. Our data provide novel insights into the function of MBD2/3 proteins and strongly suggest the existence of methylation-dependent chromatin structures in Drosophila.